The relationship between the variables of organizational trust, job engagement, organizational commitment and job involvement - Dalay, Gizem (My University, 2007)
ÖRGÜTE GÜVEN, İŞE CEZBOLMA, ÖRGÜTE BAĞLILIK VE İŞE ADANMIŞLIK ARASINDAKİ İLİŞKİLERİN İNCELENMESİ Bu çalışmada “işe cezbolma” değişkeninin “örgüte güven”, “örgüte bağlılık” ve “işe adanmışlık” değişkenleri ile arasındaki ilişkilerin incelenmesi amaçlanmaktadır. “İşe cezboma” literatürde sıklıkla kullanılan Schaufeli, Salanova, González- Romá & Bakker’ın (2002b) “Utrecht Engagement Ölçeği” (UWES) ile ölçülmüştür. Bunun yanı sıra, çalışmanın diğer değişkenlerinin ölçümü için Lodahl-Kejner’in (1965) “Job Involvement Scale” i; Buchanan’ın (1972) “Loyalty”; Hall, Scheider, & Nygren’in (1970) “Identification” ve son olarak Doboval, Comish, Swindle & Gaster’ın (1994) “Trust Inventory Survey” i kullanılmıştır. Tüm bu ölçeklerin soruları tek bir ankette birleştirilmiş ve toplam 79 soru olarak İstanbul’un en büyük kamu hastelerinden birindeki 108 çalışana uygulanmıştır. Elde edilen sonuçlar, örgüte güven ile örgüte bağlılık arasında pozitif bir ilişki bulunduğunu ortaya koymuştur. İşe cezbolmanın bazı boyutları ile örgüte bağlılık arasında pozitif ilişkiler vardır. Örgüte bağlılığın, örgüte güven ve işe cezbolma arasında kısmi ara değişken işlevi gösterdiği görülmüştür. Son olarak ise, işe adanmışlığın, örgüte bağlılığın “özdeşleşme” boyutu ile işe cezbolmanın “canlılık” boyutu arasında şartlı değişken rolünü üstlendiği belirlenmiştir.

THE RELATIONSHIP BETWEEN THE VARIABLES OF ORGANIZATIONAL TRUST, JOB ENGAGEMENT, ORGANIZATIONAL COMMITMENT AND JOB INVOLVEMENT The main purpose of this study was to examine job engagement’s relationship with the variables of organizational trust, organizational commitment, and job involvement. The measurement of job engagement has been made by the most common measure of Schaufeli, Salanova, González- Romá & Bakker’s (2002b) Utrecht Engagement Scale (UWES). Moreover, Lodahl-Kejner’s (1965) “Job Involvement Scale”, Buchanan’s (1972) “Loyalty” scale, Hall, Schneider, & Nygren’s (1970) “Identification” scale, and at last Doboval, Comish, Swindle & Gaster’s (1994) “Trust Inventory Survey” have been used for the measurement of the other variables of the study. All of these measurements have been gathered together in a 79 item survey and applied to 108 employees of one of the biggest public hospitals of Istanbul. The results showed that organizational trust is positively related with organizational commitment. There are positive relationships between some factors of job engagement and organizational commitment. Organizational commitment partially mediates the relationship between organizational trust and job engagement. Finally, job involvement moderates the relationship between “identification” factor of organizational commitment and “vigor” factor of job engagement.
Keywords: Örgüte Güven; Örgütsel Bağlılık; Örgütsel Davranış